Do post-prison job opportunities reduce recidivism? - Kevin Schnepel (IZA World of Labor, 2017)
The majority of individuals released from prison face limited employment opportunities and do not successfully reintegrate into society. The inability to find stable work is often cited as a key determinant of failed re-entry (or “recidivism”). However, empirical evidence that demonstrates a causal impact of job opportunities on recidivism is sparse. In fact, several randomized evaluations of employment-focused programs find increases in employment but little impact on recidivism. Recent evidence points to wages and job quality as important determinants of recidivism among former prisoners.
Keywords: J23; J24; K42; 330; crime; recidivism; prisoner re-entry; employment